Generative Learning and Living Approaches of Excluded People of Karnali Province - Jageshwor Upadhyaya (Surkhet Journal, 2025)
This paper offers a focused exploration of marginalized communities. It highlights their remarkable resilience and agency through context-specific, generative approaches to learning and research. These approaches often employ decolonial and participatory methods, specifically honoring indigenous knowledge and challenging dominant narratives to foster local empowerment and sustainable development. The primary purpose of this study is to examine the causes and consequences of exclusion on the lives of individuals in Karnali Province, with a particular focus on learning and living ways. By using generative, context-specific methods for learning and research, it demonstrates their extraordinary agency and resilience. In Karnali Province, innovative teaching methods like Teachers' Professional Development (TPD) and customized training are emerging, emphasizing the need for locally designed curricula that integrate indigenous knowledge, practical skills, and digital literacy. Policy adjustments are crucial to provide the necessary funding and infrastructure for these transformations. In order to trace out the political inequality of marginalized groups and to generalize the findings, both primary (in depth interview) and secondary qualitative data (printed journals and books and online materials) have been interpreted and analyzed. The key informant interview method was employed to explore the condition of excluded people on the current province government political inequality, identity debates, and representation. It emphasizes the base of inequality in society for the development process is the mindset of the planner and implementation of the constitutional provision for inclusion.